Barriers to participating in the collection of traceable catch landing data for sharks and rays: focus group discussions (FGD) of small-scale fishers in Pahang, Malaysia - Yusof, Roba’a; Ahmad Shuib; Ahmad Ali; Ismail, Illisriyani; Ramachandran, Sridar (Penerbit UMT, 2022)
The objective of this study is to identify barriers in participating in the collection of traceable catch landing data for shark and ray species among small-scale fishers in Pahang, Malaysia. As one of the major shark catchers in the world, Malaysia has been recommended to implement a traceability system to manage its supply chain process, starting from catch landings, to ensure sustainable fishing of sharks and rays. The participation of of small-scale fishers in this effort is crucial due to the significant impact of shark and ray population to their livelihood, even though they have limited capability to record catch data due to lack of resources and education. A purposive snowball sampling was used to identify participants for focus group discussions (FGD). A semi-structured open-ended proforma was used as a discussion guide. The findings suggest that there are five barriers to participation, namely (i) shark and ray resources; (ii) governance and management support; (iii) infrastructure and management information system; (iv) fishers’ commitment and buy-ins; and, (v) collaboration effort among stakeholders. It is important for policymakers to consider mandatory registration of shark and ray fishers, besides encouraging them to report their catch up to species level with incentives and training programs, as well as information technology improvements, to overcome the barriers. Future studies might expand into quantitative analysis and include other players in the shark and ray supply chain.